ANALISIS PENGARUH KEBIJAKAN HUTANG, PERTUMBUHAN PENJUALAN( GROWTH SALES) DAN DENGAN RETURN ON EQUITY - Andriasari, Widi Savitri; Mawardi, Miyasto Wisnu (JURNAL BISNIS STRATEGI, 2016)
Stock return is the result of profit or loss obtained from a stock investment.This study aimed to examine the effects of Debt Policy, Sales Growth (GS), and Return on Assets (ROA) to Stock Return used Return on Equity (ROE) as an intervening variable in the study of manufacture companies listed on the Stock Exchange Year 2010-2014.The population in this research is manufacturing companies listed in Indonesia Stock Exchange in accordance Indonesian Capital Market Directory (ICMD). The data used in the study is time series data and cross section (pooling data), and purposive sampling method based on the criteria mentioned above, the number of samples used as many as 32 companies. Analyze techniques using multiple regression, the classic assumption test, and Sobel test.The results of this research partially first model shows that the Debt to Equity Ratio (DER) and Sales Growth (GS) had no significant effect on Return on Equity (ROE), while Return on Assets (ROA) have a significant effect on Return on Equity (ROE) , The second model shows that the Debt to Equity Ratio (DER) and Return on Assets (ROA) no significant effect on Stock Return, whereas Sales Growth (GS) and Return on Equity (ROE) significant effect on stocks return. The results showed that simultaneous Debt to Equity Ratio (DER), Sales Growth (GS), Return on Assets (ROA) and Return on Equity (ROE) significantly affects the Stock Return